Impact evaluation of the routine hepatitis B vaccination program of infants in China. (27th January 2018) - Sun, Mei; Li, Chengyue; Dan Wu,; Li, Pingping; Lu, Jun; Wang, Ying; Chang, Fengshui; Li, Xiaohong; Hao, Mo
Abstract: Background: To evaluate the impact of the routine hepatitis B vaccination program of infants in China. Methods: The incidence of new hepatitis B infection and coverage with three doses of the vaccines by age groups and provinces were derived from the National Network Direct Report System of Infectious Disease during 2004–10. Chi square test and Pearson correlation analysis were used to analyze differences in incidence according to vaccination coverage and the relationship between the coverage with three doses and the incidence in different provinces. Results: The incidence of new infection was 8.96/100 000 among children with complete coverage (0–15 years old), which was significantly lower than that with partial or no coverage. Among 0–9-year-old children in 2010, the incidence of new infection was 6.36/100 000, which was significantly lower than 2004. Considering the impact of vaccination on cumulative incidence among 0–5-year-old children, a 2.2-fold greater incidence of new infection was observed in provinces with the lowest to the highest vaccination rate. Conclusion: The impact of the routine hepatitis B vaccination program of infants in China has become more apparent over time. Program implementation and regional disequilibrium should be payed attention to as well as the expanded program.